Tillit mellom profesjoner: Sosial verdiskaping i tverrfaglig arbeidsveiledning (ABV) (Tidsskrift for Praktisk Teologi, 2023)
This article answers the research question: "How do participants experience interdisciplinary ABV, and how can these experiences be understood as social capital?"We have reported from qualitative interviews with twelve participants in interdisciplinary ABV groups and analyzed their statements as a formative process with concepts from the social capital theory.For the participants, interdisciplinary ABV represents a new network and norms that activate generalized collaboration in contrast to the particular form of collaboration in their everyday staff. A bridging trust is created in two forms: support from others and a broader understanding of the person and the role of others. Over time, as the group settles, a new form of binding trust is created. A clearer "we" emerges in the group. With this "we", the group members gain an expanded understanding of themselves. Through this work, the informants admit that something also develops in their relationship with their home staff: they understand more of their colleagues and become better colleagues themselves.